Теоретико-методические основы подготовки студентов к научно-педагогической деятельности в среде многообразия - Турковский, Веслав Иосифович (International Dialogues on Education Journal, 2016)
Theoretical and methodological bases of preparing students for research and teaching activities in a diverse cultural environment): The readiness of university students of pedagogical specialties for research activities are the backbone basis for professional pedagogical activity. This is determined by the complexity and contradictions of modern life, and of the socio-cultural and educational environment. The considerable creativity in a diverse environment is conditioned by a combination of negative factors. The dynamic diversity of the environment and its diverse impact on individual and social groups require a revision of the existing educational technologies, means and forms of teacher education. New systems of teaching students will be effective when they are built on leading theoretical and methodological models of professional activity.